El trinomio realidad, leyenda y fantástico en “Pablito clavó un clavito: una evocación del Petiso Orejudo” (2016), de Mariana Enríquez - Bolognesi, Sara (2022)
This article proposes a critical reading of the interlocking of the fantastic genre and a famous Argentine urban legend, starring the serial killer Cayetano Santos Godino, within the short story’s plot “An invocation of Big-Eared Runt”, included in Things we lost in the fire (2016), by Mariana Enríquez. Specifically, this research analyses the supernatural elements that compose the plot, with the aim of showing that they have not only an aesthetic or entertainment purpose but also a socio-political intention. The paranormal, in fact, motivates the reader to look at the intimacy of a monstrous couple, because of the ghostly company of the infanticide and the precariousness in which the protagonist and his wife live their unhealthy relationship. So that, horror permeates not only the atmosphere and style of the story but also destroys family and emotional ties, clouds the mind of the main character, and suggests the tragic fate of his son.The research’s theoretical framework will include the purpose of fantastic genre, mainly through the classic studies of Sigmund Freud, H. P. Lovecraft, and Tzvetan Todorov, and more contemporary ones, such as those of Teodosio Fernández and David Roas. Likewise, the investigations of Pascuala Morote Magán and Javier Gómez Ferri will be used to define the urban legend’s characteristics. Consequently, the research will conclude that the fantastic and the legend are liminal genres, because they are anchored to reality but propose a dialogue with the extraordinary to show an unstable reality and the possibility of an alternative order, where nothing is what it seems and no one can trust, not even oneself.